A reconciled estimate of ice-sheet mass balance - Shepherd, Andrew; Ivins, Erik R; A, Geruo; Barletta, Valentina R; Bentley, Mike J; Bettadpur, Srinivas; Briggs, Kate H; Bromwich, David H; Forsberg, René; Galin, Natalia; Horwath, Martin; Jacobs, Stan; et al. (Science (American Association for the Advancement of Science), 2012)
We combined an ensemble of satellite altimetry, interferometry, and gravimetry data sets using common geographical regions, time intervals, and models of surface mass balance and glacial isostatic adjustment to estimate the mass balance of Earth's polar ice sheets. We find that there is good agreement between different satellite methods--especially in Greenland and West Antarctica--and that combining satellite data sets leads to greater certainty. Between 1992 and 2011, the ice sheets of Greenland, East Antarctica, West Antarctica, and the Antarctic Peninsula changed in mass by -142 ± 49, +14 ± 43, -65 ± 26, and -20 ± 14 gigatonnes year(-1), respectively. Since 1992, the polar ice sheets have contributed, on average, 0.59 ± 0.20 millimeter year(-1) to the rate of global sea-level rise.